Effect of Twisting Phases on the Polarization Dynamics of a Vector Optical Field - Quanbin Liu; Khian-Hooi Chew; Yingqi Huang; Caixia Liu; Xiaobo Hu; Yuhua Li; Rui-Pin Chen (Photonics, 2022)
The effect of twisting phases on the polarization dynamics of a vector vortex beam with a spatially variant state of polarization (SoP) is investigated theoretically and experimentally. The twisted vector vortex optical field with the cross-phase modulation is experimentally generated and observed. The presence of the twisting phases on the vector optical field results in novel propagation dynamics and the evolution of polarization states. The optical field performs the process of compressing and stretching the orthogonal polarization components and the linear-circular polarization conversions during propagation. Different from the scalar twisted beams, the orthogonal polarization components of twisted vector beams can be compressed along the same azimuthal angle or the orthogonal azimuthal angles, depending on the signs of the twist intensity coefficients. For an anisotropic twisted optical field, the SoP and the optical field rotate, and the rotation behaviors are sensitively dependent on the twisting coefficients. Furthermore, the two vortex topological charges embedded within the orthogonal polarization component of a twisted vector vortex beam can be simultaneously identified by looking at the interference fringes of the twisting phases. This work reveals that a vector vortex beam and its SoP can be dynamically manipulated by twisting phases.